The Family Based Overweight Intervention Overweight Knowledge (f-book) on Nutritional Status in the Adolescent Age Group: Family Based Overweight Intervention Overweight Knowledge (f-book) on Nutritional Status in the Adolescent Age Group - Rosalini , Wike; Septianing Faradina, Daniar; Aji Permana, Roby (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction : The rate of overweight and obesity among Indonesian teenagers continues to increase. Overweight and obesity are often long-term and common problems experienced by teenagers. Excessive weight gain can lead to obesity and the emergence of Non-Communicable Diseases (NCDs), which are one of the causes of death worldwide. Objective : This study aims to. Based on this phenomenon, this study aims to examine the Family Based Overweight and Knowledge (F-Book) Overweight Intervention in the Adolescent Group. Method : This research uses the Pre Experiment method Design with One Group Pre-test Post-test Design approach . Results : Based on the research results, because the value of 0.020 is smaller than <0.05, it can be concluded that "Ha is accepted". This means that there is a difference in nutritional status in adolescents before and after being given intervention. Conclusion: Family Based Overweight Intervention Overweight Knowledge (f-book) affects nutritional status